Comprendemos el mundo bipolar - Quicha Castañeda, Geraldine Fabiana (2020)
The lesson entitled "We understand the Bipolar world" was developed in the fifth grade of high school as part of the subject of Social Sciences, considering the competence "To construct historical interpretations". Moreover, the following objectives were achieved: To use several sources that allow them to inquire about the Cold War, to explain the todays changes, permanence and relationships since the Cold War period and to elaborate explanations, facts and historical processes about the aforementioned subject. The lesson develops one of the most important events in Universal History. In it, we will find events such as the formation of blocs, political and economic alliance as well as; the most important military conflicts that occurred during the Cold War, which caused great tension between the communist bloc and the capitalist bloc. During the development of this lesson, I applied motivating and challenging activities that stimulated and promoted in the students the achievement of the purpose established in the learning lesson. Also, pedagogical purposes such as: motivation, recovery of previous knowledge, problematization, purpose and organization, management and follow-up by the teacher were applied. Finally, an active and meaningful participation was achieved by the students individually and collectively, with the intention of promoting student learning and the purpose we have as educators.